1978
DOI: 10.1111/j.1600-0447.1978.tb06887.x
|View full text |Cite
|
Sign up to set email alerts
|

Depressive syndrome in schizophrenia

Abstract: A depressive syndrome, closely resembling melancholia, was found in a large proportion of chronic schizophrenic men. Depression was most prominent during acute psychotic phases and was characterized by a delusional core of worthlessness and guilt. The depressive syndrome may persist throughout the patient's psychotic life and appears to be an integral component of schizophrenic psychopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

1981
1981
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 8 publications
0
8
0
2
Order By: Relevance
“…Schizophrenia is characterised by diverse psychopathology with symptoms that are commonly divided into five dimensions: positive symptoms, negative symptoms, cognitive symptoms, aggressive symptoms and affective symptoms 3. Depressive symptoms (seen as one end on the spectrum of affective symptoms) frequently accompany schizophrenia, may be part of the prodromal symptomology, following an acute episode, or occur between psychotic episodes 4. Although not as dramatic as positive and aggressive symptoms, it should be noted that the depressive symptoms of schizophrenia have been reported to be associated with various less favourable outcomes in schizophrenia 5–7.…”
Section: Introductionmentioning
confidence: 99%
“…Schizophrenia is characterised by diverse psychopathology with symptoms that are commonly divided into five dimensions: positive symptoms, negative symptoms, cognitive symptoms, aggressive symptoms and affective symptoms 3. Depressive symptoms (seen as one end on the spectrum of affective symptoms) frequently accompany schizophrenia, may be part of the prodromal symptomology, following an acute episode, or occur between psychotic episodes 4. Although not as dramatic as positive and aggressive symptoms, it should be noted that the depressive symptoms of schizophrenia have been reported to be associated with various less favourable outcomes in schizophrenia 5–7.…”
Section: Introductionmentioning
confidence: 99%
“… 4 8 Depressive symptoms have long been regarded as integral to the psychopathology associated with schizophrenia. 9 The presence of depressive symptoms in patients with schizophrenia reduces patients’ ability to function, increases the burden imposed by the underlying psychotic illness, and worsens outcomes and prognosis. 5 , 10 – 14…”
Section: Introductionmentioning
confidence: 99%
“…Although no related studies of RDC (Spitzer et al 1978) and DSM-III (APA, 1980) schizophrenics have been reported, since a depression occurring after the psychosis (though not before or during) is believed to be compatible with a diagnosis of schizophrenia, this depression is likely to occur, perhaps with similarly high frequency, in these schizophrenics. Although commonly noted in acute and good prognosis schizophrenics (McGlashan & Carpenter, 1976 a), moreover, high percentages reported in chronic patients (20-70 %; Floru et al 1975;Kayton et al 1976;Planansky & Johnston, 1978;Roy, 1980), Langfeldt nuclears (67%; Singh & Kay, 1979), and asocial schizophrenics (group mean; Klein & Rosen, 1973), plus lack of correlation with the Phillips and Strauss -Carpenter scales (McGlashan & Carpenter, 19766), further imply that this depression occurs independently of prognostic criteria or long-term outcome.…”
Section: Pharmacogenetic Depression and Pharmacogenetic Pseudoparkinsmentioning
confidence: 99%